PENGARUH LITERASI MEMBACA TERHADAP PRESTASI BELAJAR SISWA DISEKOLAH DASAR - Johanes Jufrianus Lau; Florensa Gaina; Natalidya Bolang; Natalia Fransiska Alunat; Susan Clarita Maro; Fadil Mas'ud; Rahyudi Dwiputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of reading literacy on the learning achievement of elementary school students in Indonesia. Low levels of reading comprehension, limited ability to identify key information, and minimal engagement with reading activities indicate a persistent gap between curricular expectations and students’ actual abilities. This research aims to describe students’ reading literacy levels, illustrate their academic performance, and analyze the effect of reading literacy on learning outcomes. Data on literacy and academic accomplishment were gathered from journals, publications, and empirical studies using a descriptive qualitative method and a library research strategy. The findings show that reading literacy among elementary students remains in the low-to-medium category, influenced by limited access to reading materials, insufficient family involvement, and conventional teaching methods. Studies indicate that reading literacy strongly correlates with academic achievement, contributing up to 40.5% of learning outcomes, particularly in Bahasa Indonesia and social studies. Additionally, innovative approaches such as digital gamification, augmented reality, and adaptive AI-based learning platforms have been proven to improve comprehension and student motivation significantly. The study concludes that strengthening literacy programs, integrating technology, and fostering parent teacher collaboration are essential to improving reading skills and overall academic achievement. Continued innovation and sustained literacy culture development are necessary to build a generation of independent and high-performing learners.